2015
DOI: 10.1299/mer.14-00226
|View full text |Cite
|
Sign up to set email alerts
|

Recent studies on numerical modelling of damage progression in fibre-reinforced plastic composites

Abstract: This review of previous studies on the damage and mechanical modelling of fibre-reinforced composite materials, especially carbon-fibre-reinforced plastic composites, is based on the findings of recent studies conducted in conjunction with other researchers. Studies that utilized various modelling scales, ranging from macroscopic to microscopic, are considered. The modelling of impact damage, ply cracks, ultimate tensile failure, the initiation of transverse ply cracks, the micro-mechanical properties of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…The maximum load converged for a sufficiently small mesh size, and the result agreed well with the experimental value [8]. (4) In the damage progression analysis, nonlinear analysis using the Newton-Raphson method was performed. By making the mesh sufficiently fine, it was observed that the convergence performance was improved.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The maximum load converged for a sufficiently small mesh size, and the result agreed well with the experimental value [8]. (4) In the damage progression analysis, nonlinear analysis using the Newton-Raphson method was performed. By making the mesh sufficiently fine, it was observed that the convergence performance was improved.…”
Section: Discussionsupporting
confidence: 63%
“…About 10,000 tests of material speciments are required to certificate an airframe structure [1]. To reduce the number of the experiments, simulation methods for failure analsys of CFRP have been developed [2][3][4]. It is necessary to model all these damages to accurately predict the damage of CFRP laminates.…”
Section: Introductionmentioning
confidence: 99%